Do judges enhance home advantage in European championship boxing? - Balmer, N. J.; Nevill, A. M.; Lane, A. M. (Journal of Sports Sciences, 2005)
There have been many examples of contentious points decisions in boxing. Professional boxing is scored subjectively by judges and referees scoring each round of the contest. We assessed whether the probability of a home win (and therefore home advantage) increased when bouts were decided by points decisions rather than knockouts. Overall, we found that bouts ending in points decisions had a significantly higher proportion of home wins than those decided by a knockout, though this effect varied across time, and controlling for relative quality of boxers was only effective when using more recent data. Focusing on these data, again the probability of a home win was higher with a points decision and this effect was consistent as"relative quality" varied. For equally matched boxers ("relative quality"??=??0), expected probability of a home win was 0.57 for knockouts, 0.66 for technical knockouts and 0.74 for points decisions. The results of the present study lend general support to the notion that home advantage is more prevalent in sports that involve subjective decision-making. We suggest that interventions should be designed to inform judges to counter home advantage effects.